Analisis Kebutuhan Pengembangan Media Bola-Bola Bilangan Bulat untuk Siswa Kelas IV Sekolah Dasar (Jurnal Simki Postgraduate, 2023)
Needs analysis is an important step used to find out the initial problems that an elementary school institution has. The purpose of this study was to analyze the needs of the media development of integer balls for fourth grade elementary school students. This development research uses descriptive analysis method by calculating scores using quantitative analysis. In data collection techniques using observation sheets, tests and interviews. Based on the results of the study, it showed a positive response to improving learning using the media floating integer balls for fourth grade elementary school students. This study showed that 77% of students with the first indicator were above 51% which stated students did not like mathematics, the second indicator students got a score percentage of 88% which stated students had difficulty learning integer material, the third indicator with a score percentage of 83% indicated that students had difficulty learning without using media and the last indicator with a score percentage of 94% stated that students were interested in learning to use learning media. This research can be developed to the media development stage for more optimal results.